2018
DOI: 10.3390/ijms19103228
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-Oxide: A Link among Diet, Gut Microbiota, Gene Regulation of Liver and Intestine Cholesterol Homeostasis and HDL Function

Abstract: Recent evidence, including massive gene-expression analysis and a wide-variety of other multi-omics approaches, demonstrates an interplay between gut microbiota and the regulation of plasma lipids. Gut microbial metabolism of choline and l-carnitine results in the formation of trimethylamine (TMA) and concomitant conversion into trimethylamine-N-oxide (TMAO) by liver flavin monooxygenase 3 (FMO3). The plasma level of TMAO is determined by the genetic variation, diet and composition of gut microbiota. Multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 94 publications
3
120
0
8
Order By: Relevance
“…This may be explained in part by the short time elapsed between the intake of TMAO-rich food (such as fish) or its dietary precursors (choline and carnitine found in meat and eggs), and the appearance of the metabolite in plasma, as reported by Cho et al 52 . As suggested by other authors 53 , high inter-variation in TMAO plasma levels, may be attributed to differences in gut microbiota composition and function. Some families of bacteria from Firmicutes and Proteobacteria phyla are potent choline and carnitine consumers, and are able to synthetize TMA through the expression of specific enzymes.…”
Section: Tmao In Plasma No Significant Differences In Fasting Tmao Csupporting
confidence: 55%
“…This may be explained in part by the short time elapsed between the intake of TMAO-rich food (such as fish) or its dietary precursors (choline and carnitine found in meat and eggs), and the appearance of the metabolite in plasma, as reported by Cho et al 52 . As suggested by other authors 53 , high inter-variation in TMAO plasma levels, may be attributed to differences in gut microbiota composition and function. Some families of bacteria from Firmicutes and Proteobacteria phyla are potent choline and carnitine consumers, and are able to synthetize TMA through the expression of specific enzymes.…”
Section: Tmao In Plasma No Significant Differences In Fasting Tmao Csupporting
confidence: 55%
“…Changes in gut microbiota composition (to an unfavorable gut microbial environment), or gut dysbiosis, have been linked to CVD, obesity, and T2DM [11,75]. In this sense, metabolites produced by the microbiota in obese individuals can affect cardiovascular health by enhanced inflammatory response [76,77], insulin resistance [78,79], liver fat accumulation [80], and increased plasma lipid levels [81,82].…”
Section: Nut Composition and Its Implication On Body Weight And Cardimentioning
confidence: 99%
“…A recent study reported that TMAO down-regulated intestinal and liver cholesterol as well as bile acid metabolism and impaired macrophage reverse cholesterol transport. TMAO can also contribute to dyslipidemia by regulating hepatic lipogenesis and gluconeogenesis [181]. Therefore, increased systemic circulation of TMAO is associated with intestinal dysbiosis, insulin resistance, hypertriglyceridemia, hepatic steatosis, NAFLD, and cancer [182][183][184].…”
Section: Systemic Circulation Related To the Microbiota-gut-liver Axismentioning
confidence: 99%